Menguji Kesiapan Pengelolaan Desa Berbasis Manajemen Modern Guna Menghadapi Era Revolusi Industri 4.0 - I Nyoman Andy Putra Bali; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study is to find out the pattern of leadership of village heads in managing their village located in the center of Denpasar, and we know today is the industrial revolution era 4.0 that allows a village to use more technology applied to the system with the aim of facilitating work, communication or activities of the business unit's activities towards the economic progress of its people and to restrain the urbanization of its young generation to get out of their villages or to lose interest in agricultural, plantation, animal husbandry, sculpting arts and salt industry sectors, so that village officials need to manage such as managing a company based on the function function of the company, namely Human Resources Management functions, Marketing, Technology, Operations / production and finance accompanied by the application of Good Coorperate Governance. This study uses a qualitative method that explores the implementation of the function of the company's function towards village management to go to the modern village towards the village located in the middle of the city of Denpasar. Data collection uses documentation techniques and in-depth interviews with village officials. The data is then analyzed qualitatively by data reduction, data presentation, and drawing conclusions and including theoretical and practical contributions